2023
DOI: 10.3390/agronomy13102658
|View full text |Cite
|
Sign up to set email alerts
|

Flavor Characteristics of Three Indonesian Cocoa Clones in Four Environments

Indah Anita-Sari,
Rudi Hari Murti,
Misnawi
et al.

Abstract: The non-aromatic genotypes are known to possess the capacity to produce aromatic cocoa beans when planted in strategic environments with specified soil compositions. Therefore, this study aimed to identify genetic responses to the flavor of cocoa beans in different growing environments. A total of three superior cocoa clones, namely the aromatic (MCC 02) and non-aromatic genotypes (Sulawesi 1 and Sulawesi 2), were used. A completely randomized block design was utilized with three replications at four locations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Other studies have confirmed the preponderant importance of temperature 23 , 25 , pH 23 and fermentation time 26 , 27 in the sensory quality of the grain using spontaneous or biochemical controlled fermentation. The effect of the expression of genetic variation in response to fermentation has been documented for the sensory quality of cacao by some studies 27 31 . However, to the best of our knowledge, the role of genetic variability in response to fermentation for Cd mitigation remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have confirmed the preponderant importance of temperature 23 , 25 , pH 23 and fermentation time 26 , 27 in the sensory quality of the grain using spontaneous or biochemical controlled fermentation. The effect of the expression of genetic variation in response to fermentation has been documented for the sensory quality of cacao by some studies 27 31 . However, to the best of our knowledge, the role of genetic variability in response to fermentation for Cd mitigation remains unexplored.…”
Section: Introductionmentioning
confidence: 99%